"The Chiesa della Madonna dei Mali (Ferrandina, Italy) in VR": Virtual Reality for inaccessible cultural heritage in peripheral areas. Issue 1 (November 2020) - Pecci, Antonio; Campanile, Ida
Abstract: Today the VR (Virtual Reality) enable us to enter into fantasy or real other worlds to experience a growing emotional and interaction involvement. Frequently, the Virtual Reality is correlated with activities and experiences that are tricky to realize, as, for example, the discovery of the sea depths or the flying on the sky, or the discover of village and landscapes thousands of km away from us. Over the last years, VR technologies have largely applicate for a digital fruition of cultural heritage. Some examples are the observation of monumental build or virtually rebuilt archaeological sites, experiences that provide impressive and innovative virtual activities. In many cases, it is a only alternative option for discovering archeological sites in private properties or dangerous to visit and to see inaccessible cultural heritage in peripheral areas. In this work, one example of application of virtual reality is discussed: The Chiesa della Madonna dei Mali (Ferrandina, near Matera). This is a famous rural chapel localized in a country area of Ferrandina, far from the classic tourist itineraries of the city, and it contains a cycle of frescoes by Pietro Antonio Ferro, one of the most important painters of the seventeenth century in Basilicata.